Hole-making and Drilling Technology for Composites : Advantages, Limitations and Potential - A. B. Abdullah, editor 256878; S. M. Sapuan, editor 427636; ScienceDirect (Online service) 7722 (Oxford : Woodhead Publishing, 2019)
Hole-Making and Drilling Technology for Composites: Advantages, Limitations and Potential presents the latest information on hole-making, one of the most commonly used processes in the machining of composites. The book provides practical guidance on hole-making and drilling technology and its application in composite materials and structures. Chapters are designed via selected case studies to identify the knowledge gap in hole-making operations in composites and to highlight the deficiencies of current methods. The book documents the latest research, providing a better understanding of the pattern and characterization of holes produced by various technologies in composite materials. It is an essential reference resource for academic and industrial researchers and professional involved in the manufacturing and machining of composites. In addition, it is ideal for postgraduate students and designers working on the design and fabrication of polymeric composites in automotive and aerospace applications.